A COMPARATIVE STUDY BETWEEN CLOSE READING WITH TEXT CODING AND KNOW/ WANT TO KNOW/ LEARN(KWL) STRATEGIES ON STUDENTS’ READING COMPREHENSION AT MAN 2 PEKANBARU - Jamin, Antoni; Yani, Titik Hardewi; Melshandika, Yola (Jurnal Manajemen Pendidikan, 2023)
This study tried to find out the comparison between the effect of using close reading and text coding and KWL strategies on students’ reading comprehension. This quantitative research involves two classes of eleventh grade at MAN 2 Pekanbaru. Observation sheet and reading comprehension test are used to collect data. The data analysis reveals that the students’ reading comprehension using KWL strategy has beneficial to help students’ reading comprehension. Two tests were given by the participants, pre test and post test. The post test result reveals that KWL strategy was improved significantly if it was compared to Close reading strategy. The teachers also mention several advantages concerning the use of KWL strategy in their teaching practice. The advantages include students’ curiosity to the topic given since it stimulated students’ prior knowledge, teach students how to share ideas with the group, stimulated students’ to participate actively in learning process. The findings of the study suggest that KWL strategy is really beneficial to help improve English teaching and learning. However, Close Reading strategy also might be implemented to improve the quality of students’ reading comprehension. Key Words: Close reading strategy, KWL strategy, reading comprehension